Contract preference for the dominant supplier subject to inventory inaccuracy - Tao, Feng; Yu, Hao; Fan, Tijun; Lai, Kin Keung (Computers & industrial engineering, 2020)
•Inventory inaccuracy is a vital factor to determine the prices and order quantities.•Retailers benefit from the improvement of their own inventory availability rates.•One retailer is better-off when the other reduces inaccuracy in consignment contract.•One retailer is worse-off when the other reduces inaccuracy in buyback contract.•Supplier’s preference for contract format depends on the inventory inaccuracy. Inventory inaccuracy is usually inevitable, and affects decision making. This paper investigates the operational decisions and contract preference in a supply chain with one supplier and two competing retailers that are subject to inventory inaccuracy. The supplier, acting as the Stackelberg leader, first decides the contract format and pricing policy. The two retailers are followers, which make their decisions simultaneously. We establish a newsvendor model to derive the equilibrium solutions analytically under the buyback contract, consignment contract and hybrid contract scenarios. Then we conduct a numerical study to illustrate the impact of inventory inaccuracy on the supplier chain members’ operational policy and the dominant supplier’s contract preference. The results show that inventory inaccuracy plays an important role in determining the retailers’ equilibrium order quantities and retail prices, and the supplier’s wholesale (consignment) price. In particular, one retailer is better off (worse off) if the other who adopts the consignment (buyback) contract improves the inventory availability. Importantly, inventory inaccuracy affects the supplier’s contracting strategy. If the inventory availability changes, then the optimal contract selection may, accordingly, be changed. The conclusions reveal that although inventory inaccuracy is assumed to have occurred on the retailer’s side, both the retailer and the supplier are greatly influenced by the inventory inaccuracy. Therefore, the supplier should fully consider inventory availability and retail competition before determining the contract format. The retailer should improve his inventory availability to enhance competitiveness, to receive a more profitable contract format from the supplier.